How difficult is China's business environment for European and American companies? - Uri Dadush; Pauline Weil (Bruegel, 2021)
Despite tensions over China's discriminatory business practices, China's trade continues to thrive, and the country has taken over from the United States as the first destination for foreign investment. American and European businesses continue to be engaged in China's large and growing market, even amid a trade war between China and the United States. Drawing on surveys of companies and international comparisons, we show that - contrary to the prevailing narrative - China's business practices have improved significantly in recent years. China's business environment is today generally more favourable than that in other large countries at similar levels of development and, in some though certainly not all aspects, is in line with the Organisation for Economic Co-operation and Development average. Differences over geopolitics and human rights must be addressed, but it is clear that trade and investment agreements conditioned on accelerated reforms in China would yield substantial dividends. The benefits of such deals would accrue not only to foreign investors in China and exporters to China, but also to consumers and importers in the European Union and, especially, in the US, where punitive tariffs on China remain in effect. Critical aspects in the negotiations would include better access for American and European investors to China's market for services and improved enforcement of rules and regulations in China. As in many middle-income countries, uneven enforcement of the law (rather than the law itself) remains a critical problem in China.
Keywords: 330